PENERAPAN TEKNOLOGI PENGOLAHAN SAMPAH ORGANIK DESA SALEM BREBES MENUJU DESA MANDIRI SAMPAH - Listiowati, Emyliana; Setyanto, Refius Pradipta; Ambarningrum, Trisnowati Budi; Pamudji, Ganjar; Susanto, Irwan; Lestari, Sri (Universitas Mataram, 2025)
Waste management is a global problem in Indonesia. Salem Village is one of the villages in Brebes Regency where waste management is not optimal. The condition of the increasingly piled up waste without processing creates an unpleasant odor and disturbs the health of the surrounding community. The waste processing carried out is burning the existing waste, which adds to the problem of air pollution. As a result of continuous waste burning, the hangar was also burned. The impact of burning waste is very dangerous because it releases monoxide gas which disturbs public health. The purpose of this program is to provide socialization of waste processing, waste banks, Village Regulations on waste management, waste processing technology based on BSF flies and maggots into exoenzyme products that have economic value. Activity methods include lectures and discussions, training, demonstration plots and mentoring. Socialization to cadres and administrators of Bumdes Bina Usaha Salem Village regarding a) independent waste management and waste bank applications; b) socialization of village regulations (perdes) governing waste management, c) dissemination of information about organic waste processing technology based on BSF maggots and Ecoenzymes.The results of the socialization showed an increase in participants' knowledge about the necessity of business management and group management, village regulations governing waste management, the bioecology of BSF maggots, and the technology of organic waste bioconversion using BSF maggots. The training and demonstration plots provided to partners included preparation for waste processing, ecoenzym production, baby maggot maintenance, organic waste processing techniques with BSF maggots, and prepupa harvesting. The evaluation of the activity showed that the pre-test scores initially ranged from 25 (5.88%) to 75 (5.88%). After the technology transfer, the post-test scores increased to a range of 60 (5.88%) to 85 (11.77%). The Community Service Program can realize the independence of the residents of Salem village in managing organic waste.